Circulating tumor cell count and thrombosis in metastatic breast cancer. (1st September 2017) - Beinse, G.; Berger, F.; Cottu, P.; Dujaric, M.‐E.; Kriegel, I.; Guilhaume, M.‐N.; Diéras, V.; Cabel, L.; Pierga, J.‐Y.; Bidard, F.‐C.
Abstract : Essentials Tumor cells circulating in blood (CTC) may favor thrombotic events in cancer patients. We assessed the impact of CTC on the risk of thrombosis in metastatic breast cancer. Baseline CTC detection was the only independent factor associated with the risk of thrombosis. CTC detection under therapy may be the hidden link between tumor progression & thrombosis. Summary: Background: Circulating tumor cell (CTC) count is a major prognostic factor in metastatic breast cancer (MBC) and has been reported to be associated with thrombosis in short‐term studies on MBC patients. Objective: To assess whether CTC detection (CellSearch ® ) before first‐line chemotherapy impacts the risk of thrombosis throughout the course of MBC. Patients/Methods: Among patients included before first‐line chemotherapy for MBC in the prospective IC2006‐04 CTC detection study (NCT00898014), the electronic medical files of those patients treated at Institut Curie (Paris, France) were searched in silico and manually checked for incident venous or arterial thrombotic events (TE) in the course of MBC. Univariate and multivariate analyses were performed using Cox and Fine‐Gray models, adjusted for age and Khorana score. Results/Conclusions: With a median follow‐up of 64 months (25–81 months), among the 142 patients included, 34 (24%) experienced a TE (incidence rate, 8 TE/100 patient‐years). The TE incidence rate was 13 TE/100 patient‐years for the 80 patients with ≥ 1 CTC/7.5 mL of blood before initiating first‐line chemotherapy, vs. only 4 TE/100 patient‐years for the 62 CTC‐negative patients. Fine‐Gray multivariate analysis (with death as competing event) included age, Khorana score and baseline lactate dehydrogenase and CTC levels: detectable CTC was the only factor significantly associated with an increased risk of TE (sub‐distribution hazard ratio [SHR] for patients with [1–4] CTC = 3.1, 95% CI [1.1; 8.6], SHR for patients with ≥ 5 CTC = 1.4, 95% CI [0.5; 4.6]). This study shows that CTC detection before starting first‐line chemotherapy is an independent risk factor for TE in MBC patients.